The Importance of Fine Ore Chemical Composition and High Temperature Phase Relations ù Applications to Iron Ore Sintering and Pelletising - J M. F Clout (The Australasian Institute of Mining and Metallurgy, 2002)
In the iron ore industry significant emphasis is placed throughout the mining process on meeting chemical composition specifications for the export of fine ores, however, little has been published on the implications of ore chemical composition for iron ore sinter and pellet product quality. The ore bulk composition, together with the nature of the minerals in the fine ore both play a critical role in determining the type of high temperature bonding phases that form during sintering and pelletising. This paper uses the experimental determination of phase relations in model sinter and pellet systems such as Fe2O3-CaO-SiO2 (FCS) and Fe2O3-Al2O3-CaO-SiO2 (FACS) to examine the links between iron ore chemical composition and the temperatures used during sintering and pellet firing. The phase relations help to establish the critical thermal and compositional parameters that control the bonding phase chemistry which in turn influences the physical characteristics of the sinter or pellet matrix. Results show that lower Fe-grade (